Note on the Numerical Solutions of Unsteady Flow and Heat Transfer of Jeffrey Fluid Past Stretching Sheet with Soret and Dufour Effects - Hossam A. Nabwey; Muhammad Mushtaq; Muhammad Nadeem; Muhammad Ashraf; Ahmed M. Rashad; Sumayyah I. Alshber; Miad A. Hawsah (Mathematics, 2022)
A numerical investigation of unsteady boundary layer flow with heat and mass transfer of non-Newtonian fluid model, namely, Jeffrey fluid subject, to the significance of Soret and Dufour effects is carried out by using the local nonsimilarity method and homotopy analysis method. An excellent agreement in the numerical results obtained by both methods is observed and we establish a new mathematical approach to obtain the solutions of unsteady-state flow with heat and mass transfer phenomenons. Similarity transformation is applied to governing boundary layer partial differential equations to obtain the set of self-similar, nondimensional partial differential equations. Graphical results for different emerging parameters are discussed. The dimensionless quantities of interest skin friction coefficient, Sherwood number, and Nusselt number are discussed through tabulated results. The main novelty of the current work is that the average residual error of the <semantics>mth</semantics>-order approximation of the OHAM scheme for steady-state solution is decreased for higher-order approximation. Further, a rapid development of the boundary layer thickness with the increasing values of dimensionless time <semantics>τ</semantics> is observed. It is noted that for large values of <semantics>τ</semantics>, the steady state in the flow pattern is gained. It is worth mentioning that the magnitude of Sherwood number is increased with the increasing values of Schmidt number <semantics>Sc</semantics> and Dufour number <semantics>Df</semantics>. The magnitude of local Nisselt number is increased for the increasing values of Soret number, <semantics>Sr</semantics>.